Positive electrode active material and preparation method thereof, positive plate and battery

By defining the exposure degree of a specific crystal surface and regulating the valence state of manganese ions, a positive electrode active material was prepared, which solved the problem of lithium nickel manganate due to structural instability and low rate performance, and achieved a battery with high rate performance and discharge capacity.

CN119812298APending Publication Date: 2025-04-11NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411997946.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The electrolyte decomposition and crystal structure instability due to the high operating voltage of spinel nickel manganate limits its commercial application, and improving structural stability through coating and doping will reduce the rate performance.

Method used

By defining the exposure level of a specific crystal surface, a positive electrode active material is prepared that satisfies a specific XRD pattern intensity ratio, including trivalent manganese ions and tetravalent manganese ions, and regulates the disorder of the material through a specific sintering process.

Benefits of technology

It significantly improves the rate performance and discharge capacity of the battery, improves the conduction rate and charge storage capacity of lithium ion, and enhances the pressure resistance and cycling performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812298A_ABST
    Figure CN119812298A_ABST
Patent Text Reader

Abstract

The invention provides a positive active material and a preparation method thereof, a positive plate and a battery. The positive electrode active material satisfies the following condition: # imgabs0 #, wherein I (111), I (222), I (400) and I (440) are all not 0. According to the positive electrode active material provided by the invention, the exposure degrees of the crystal face (222) and the crystal face (111) relative to the crystal face (110) and the crystal face (100) are limited by the formula 1, so that the lithium ion conduction rate and the dynamic performance of lithium nickel manganese oxide can be improved, and the rate capability and the discharge capacity of a corresponding battery can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery materials, and in particular to a positive electrode active material and a preparation method thereof, a positive electrode sheet and a battery. Background Art

[0002] In the new energy industry, the widespread use of electric vehicles has brought great convenience and benefits. However, with the updating and development of technology, the market has put forward higher requirements for electric vehicles. Mileage and charging time are the two most important concerns of consumers.

[0003] Spinel nickel manganese oxide has high operating voltage and high energy density, and has a stable 3D lithium ion transmission channel. Therefore, it has broad application prospects in electric vehicles, energy storage systems, and portable electronic devices. However, the commercialization of lithium nickel manganese oxide is hindered by the decomposition of the electrolyte caused by the high operating voltage and the unstable crystal structure (Jiang Taylor effect). The structural stability of spinel nickel manganese oxide can be effectively improved by coating and doping, but coating and doping will significantly reduce the rate performance of lithium nickel manganese oxide batteries. Summary of the invention

[0004] The present invention provides a positive electrode active material, which can significantly improve the rate capability and discharge capacity of a battery by limiting the exposure degree of a specific crystal face.

[0005] The present invention also provides a method for preparing the positive electrode active material. The method can prepare the positive electrode active material and has a simple process.

[0006] The present invention also provides a positive electrode sheet. Since the positive electrode sheet includes the positive electrode active material, it has the advantages of fast ion transmission rate and high charge storage capacity.

[0007] The present invention also provides a battery. Since the battery includes the positive electrode sheet, the battery has both high rate performance and discharge capacity.

[0008] In a first aspect, the present invention provides a positive electrode active material, wherein the positive electrode active material satisfies the following

[0009] Formula 1:

[0010]

[0011] Among them, I (111) ,I (222) ,I (400) and I (440) Both are not 0.

[0012] Furthermore, the positive electrode active material includes trivalent manganese ions and tetravalent manganese ions, and the mass ratio of the trivalent manganese ions to the tetravalent manganese ions increases from the center to the outer surface of the positive electrode active material.

[0013] Furthermore, the chemical composition of the positive electrode active material includes: Li a Ni b Mn c M d O 4-h ;

[0014] Among them, 1.0≤a≤1.006, 0.495≤b≤0.505, 1.495≤c≤1.505, 0≤d≤0.003, -0.082<h<0.21, b+c=2, and M is selected from at least one of W, Mo, Ta, Nb, V, and Sb.

[0015] Furthermore, the disorder degree of the positive electrode active material is 6%-9%.

[0016] In a second aspect, the present invention provides a method for preparing the positive electrode active material as described in the first aspect, comprising the following steps:

[0017] The mixed material including the nickel manganese hydroxide precursor and the first lithium source is heated to m°C at a heating rate of 1-5°C / min in an oxygen-containing atmosphere, and sintered once to obtain an intermediate; the first lithium source is calculated as lithium element, the nickel manganese hydroxide precursor is calculated as the sum of nickel element and manganese element, and the molar ratio of the nickel manganese hydroxide precursor to the first lithium source is 2:0.8-0.95;

[0018] The mixed material including the intermediate and the second lithium source is heated to n°C at a heating rate of 1-5°C / min in an oxygen-containing atmosphere and sintered twice to obtain the positive electrode active material; wherein the molar ratio of the intermediate and the second lithium source is 0.05-0.2, and n is less than m.

[0019] Furthermore, the first lithium source is calculated as lithium element, the nickel manganese hydroxide precursor is calculated as the sum of nickel element and manganese element, and the molar ratio of the nickel manganese hydroxide precursor to the first lithium source is 2:0.85-0.9.

[0020] Furthermore, m satisfies: 950≤m≤1050.

[0021] Furthermore, the n satisfies: 750≤n≤850.

[0022] In a third aspect, the present invention provides a positive electrode sheet, comprising a current collector and a positive electrode active layer disposed on at least one surface of the current collector; the positive electrode active layer comprises the positive electrode active material as described in the first aspect.

[0023] In a fourth aspect, the present invention provides a battery, comprising the positive electrode sheet as described in the third aspect.

[0024] The positive electrode active material provided by the present invention defines the exposure degree of the (222) crystal plane and the (111) crystal plane relative to the (400) crystal plane and the (440) crystal plane by formula 1, which can improve its lithium ion conduction rate and charge storage capacity, and thus can significantly improve the rate performance and discharge capacity of the corresponding battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0026] Figure 1 is a SEM image of the positive electrode active material of Example 1;

[0027] Figure 2 is a SEM image of the positive electrode active material of Comparative Example 1;

[0028] Figure 3 is a SEM image of the positive electrode active material of Example 2;

[0029] Figure 4 is a SEM image of the positive electrode active material of Comparative Example 2;

[0030] Figure 5 1 is a XRD comparison diagram of the positive electrode active materials of Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0031] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0032] Lithium nickel manganese oxide presents a spinel octahedral structure, which mainly includes three crystal planes (100), (110) and (111). Different crystal planes have different lithium ion transmission rates, which is caused by the different atomic stacking densities of different crystal planes. Among them, (111) has more Ni / Mn atomic stacking and a large atomic density. Therefore, lithium ions are relatively slow to transmit on this crystal plane, but the (111) crystal plane is more stable, and the atomic density of the (100) crystal plane and the (110) crystal plane is lower than that of the (111) crystal plane, so the two have a higher lithium ion transmission rate, but due to the low atomic density and high reaction activity, it will cause the Jan-Taylor effect, resulting in the dissolution of Mn, so the stability of the (100) crystal plane and the (110) crystal plane is poor. The present invention finds that by regulating the polycrystalline planes of the positive electrode active material, its kinetic performance can be comprehensively improved. In detail, the present invention adopts the following technical scheme:

[0033] In a first aspect, the present invention provides a positive electrode active material, wherein the positive electrode active material satisfies the following

[0034] Formula 1:

[0035]

[0036] Among them, I (111) ,I (222) ,I (400) and I (440) Both are not 0.

[0037] It should be noted that, in Formula 1, the I (111) It refers to the diffraction peak intensity of the (111) crystal plane in the XRD spectrum of the positive electrode active material. Its intensity is measured by the height of the diffraction peak. Further, I (111)+ I (222) It refers to the sum of the diffraction peak intensity of the (111) crystal plane and the diffraction peak intensity of the (222) crystal plane in the XRD spectrum of the positive electrode active material. (400) ,I (400) +I (440) In addition, in the XRD spectrum, since the (110) and (100) planes are low-index crystal planes and are at a lower 2-Theta angle, they are difficult to identify. The (400) crystal plane is the fourth-order diffraction crystal plane of the (100) crystal plane, and the (440) crystal plane is the fourth-order diffraction crystal plane of the (110) crystal plane. Therefore, the present invention selects (440) and (400) to replace (110) and (100) for definition.

[0038] In the present invention, the exposure degree of the (111) plane and the (222) plane relative to the (400) crystal plane and the (440) crystal plane can be limited by formula 1, which helps to improve the rate performance and specific capacity of the positive electrode active material. The reason is that the (100) crystal plane and the (110) crystal plane of the positive electrode active material respectively reflect the truncated corner and edge components of the particle morphology, and the (111) crystal plane and the (222) crystal plane reflect the regular octahedral component. The atomic arrangement of the (111) crystal plane is denser, the crystal plane is more stable, and the Jan-Taylor effect is not obvious. The positive electrode active material satisfying formula 1 With more truncated and truncated morphologies, lithium ions are easier to insert and remove. Therefore, the rate performance and discharge capacity of the positive electrode active material are greatly improved compared with the traditional octahedral nickel manganese oxide. In addition, the positive electrode active material that satisfies Formula 1 also reasonably controls the exposure degree of the (100) crystal plane and the (110) crystal plane relative to the (111) crystal plane and the (222) crystal plane, which can improve the pressure resistance of the material to a certain extent, thereby reducing the breakage of the positive electrode active material particles caused by mechanical stress during the coating process, thereby increasing the side reactions and reducing the cycle performance.

[0039] In some optional embodiments, the positive electrode active material includes trivalent manganese ions and tetravalent manganese ions, and the mass ratio of the trivalent manganese ions to the tetravalent manganese ions increases from the center to the outer surface of the positive electrode active material.

[0040] The increasing mass ratio of trivalent manganese ions to the quadrivalent manganese ions from the center to the outer surface of the positive electrode active material can also be understood as: the ratio of the disordered phase to the ordered phase structure increases from the center to the outer surface of the positive electrode active material. In addition, the "increasing" in the present invention only represents that the mass ratio trend of trivalent manganese ions is increasing. As for whether it is a regular curved increase or a regular increase, the present invention does not make specific limitations on this.

[0041] In the embodiment described above, since the positive electrode active material includes trivalent manganese ions, and the trivalent manganese ions increase from the inside to the outside, the positive electrode active material can have better electrochemical activity, and the trivalent manganese ions can participate in the redox reaction during the charge and discharge process, thereby contributing to the capacity; at the same time, the lithium nickel manganese oxide in the form of trivalent manganese ions has a disordered phase structure, and the structural phase change is stable during the charge and discharge process, so the cycle performance can be improved.

[0042] The concentration of trivalent manganese ions increases gradually and can be tested by the following method:

[0043] X-ray photoelectron spectroscopy (XPS) was used to characterize and test the valence and content of manganese in samples with different etching depths. The Mn 4+ / Mn 3+ ratio, thereby inferring the change in the mass ratio of trivalent manganese ions to tetravalent manganese ions.

[0044] In some embodiments, from the outer surface to the center of the positive electrode active material, the Mn at 2 nm from the outer surface 4+ / Mn 3+ The ratio of C2 is defined as the Mn at 20 nm from the outer surface. 4+ / Mn 3+ The ratio is defined as C1, C2-C1 satisfies: 0.1≤C2-C1≤0.3.

[0045] In some optional embodiments, the chemical composition of the positive electrode active material includes: Li a Ni b Mn c M d O 4-h ;

[0046] Among them, 1.0≤a≤1.006, 0.495≤b≤0.505, 1.495≤c≤1.505, 0≤d≤0.003, -0.082<h<0.21, b+c=2, and M is selected from at least one of W, Mo, Ta, Nb, V, and Sb.

[0047] In some embodiments, the positive electrode active material includes a core and a shell located on the surface of the core, and the element M is located in the shell of the positive electrode active material. The shell includes the doping element M, which is beneficial to further improve the electronic conductivity and ionic conductivity of the positive electrode active material, thereby improving the rate performance of the battery.

[0048] In some embodiments, when conventional lithium nickel manganese oxide has the same chemical composition as the positive electrode active material of the present invention as described above, the rate performance of the positive electrode active material as described above can be improved by 1%-5%, wherein the rate performance W is defined as W=2C / 0.1C*100.

[0049] In order to further improve the lithium ion transport and energy storage properties of the positive electrode active material, in a preferred embodiment, d=0.003.

[0050] Ordered lithium nickel manganese oxide generally has a cubic spinel structure with a P4332 space group, in which lithium ions occupy octahedral sites, and disordered lithium nickel manganese oxide has a Fd3m space group, which also has a cubic spinel structure, but the nickel and manganese ions therein are disorderedly distributed in the lattice. Ordered lithium nickel manganese oxide generally has a higher energy density because its voltage platform is higher, while disordered lithium nickel manganese oxide is more conducive to lithium ion diffusion and transportation, and therefore has better rate performance, but too much disordered phase Jiang-Taylor effect is serious, the chemical stability of the structure deteriorates, and the electrochemical performance deteriorates, so the ratio of ordered / disordered structure should be controlled. In some optional embodiments, the disorder degree of the positive active material is 6%-9%.

[0051] Among them, as mentioned above, the disordered positive electrode active material has more conductive paths, which helps to further improve the electronic conductivity of the positive electrode active material, thereby further improving the rate performance of the battery.

[0052] Exemplarily, the disorder degree of the positive electrode active material is any value of 6%, 7%, 8%, 9%, etc., or a range consisting of any two of them.

[0053] In some embodiments, the disorder of the positive electrode active material is tested by the following method:

[0054] The fully ordered lithium nickel manganese oxide positive electrode active material is assembled into a positive electrode sheet, and then the positive electrode sheet is assembled into a battery cell 1. Then, the positive electrode active material of the present invention is assembled into a positive electrode sheet in the same steps, and then the positive electrode sheet is assembled into a battery cell 2. The proportion of the charging capacity of the battery cell 1 at 4.4V in the first cycle to the total charging capacity of the first cycle is defined as X 1 The proportion of the first cycle charging capacity of cell 2 below 4.4V in the first cycle total charging capacity is defined as X 2 , then the disorder degree σ=(X 2 -X 1 ) / X 1 .

[0055] In a second aspect, the present invention provides a method for preparing the positive electrode active material as described in the first aspect, comprising the following steps:

[0056] The mixed material including the nickel manganese hydroxide precursor and the first lithium source is heated to m°C at a heating rate of 1-5°C / min in an oxygen-containing atmosphere, and sintered once to obtain an intermediate; the first lithium source is calculated as lithium element, the nickel manganese hydroxide precursor is calculated as the sum of nickel element and manganese element, and the molar ratio of the nickel manganese hydroxide precursor to the first lithium source is 2:0.8-0.95;

[0057] The mixed material including the intermediate and the second lithium source is heated to n°C at a heating rate of 1-5°C / min in an oxygen-containing atmosphere and sintered twice to obtain the positive electrode active material; wherein the molar ratio of the intermediate and the second lithium source is 0.05-0.2, and n is less than m.

[0058] The above preparation method controls the amount of the first lithium source added to the mixed material and the temperature of the first sintering so that the synthesized intermediate is a lithium-deficient nickel-manganese spinel and constructs a polycrystalline face morphology, and then adds the second lithium source and performs a second sintering at a lower temperature to complete the synthesis of a polycrystalline face lithium nickel manganese oxide nickel manganese spinel with a disordered surface phase, wherein the chemical composition of the positive electrode active material includes: Li a Ni b Mn c Md O 4-h , and d is not 0. The mixed material for secondary sintering also includes an M source. The M source has a fluxing effect and can cooperate with the second lithium source to make the (110)(100) crystal planes of the positive electrode active material easier to form and can regulate the formation of the (111) plane, construct a cross-section with a high lithium ion diffusion coefficient, and avoid forming (110) and (100) crystal planes that are too wide and too long. At the same time, it will be doped in the surface interface of lithium nickel manganese oxide. Due to the effect of charge compensation, a disordered phase spinel structure will be formed. At the same time, the second lithium source supplements lithium for the intermediate, making the surface of the positive electrode material lithium-rich, further improving the lithium ion diffusion coefficient of the positive electrode active material.

[0059] It can be understood that since the above intermediate is a lithium-deficient lithium nickel manganese spinel, a second lithium source needs to be added for lithium supplementation. As for the amount of the second lithium source added, the technician can calculate it based on the target chemical structure of the finished product and the difference in the chemical structure of the intermediate, and the present invention does not make specific limitations on this.

[0060] Exemplarily, the first lithium source and the second lithium source are both lithium-containing substances, which may be the same or different, for example, including at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium oxalate, and lithium citrate, preferably at least one of lithium carbonate and lithium hydroxide.

[0061] The M source may be a compound of M, and preferably an oxide of M.

[0062] The nickel manganese hydroxide precursor is a hydroxide containing Ni and Mn elements, and the chemical formula may be Ni x Mn y (OH) z , 0.495≤x≤0.505, 1.495≤y≤1.505, z=2, x+y=2.

[0063] In some embodiments, the molecular formula of the above intermediate is: Li a Ni b Mn c O 4-h , among which, 0.8≤a≤0.95, 0.495≤b≤0.505, 1.495≤c≤1.505, 0.025<h<0.1.

[0064] In some embodiments, the primary sintering and / or secondary sintering further includes cooling and crushing steps.

[0065] In some optional embodiments, the first lithium source is calculated as lithium element, the nickel manganese hydroxide precursor is calculated as the sum of nickel element and manganese element, and the molar ratio of the nickel manganese hydroxide precursor to the first lithium source is 2:0.85-0.9.

[0066] The above-described embodiments can further control the proportion of disordered phase on the surface of the positive electrode active material, thereby further avoiding the occurrence of structural collapse or irreversible phase change of the positive electrode active material during the cycle process.

[0067] In order to further ensure that the intermediate can be formed into lithium-deficient nickel-manganese spinel, in some optional embodiments, m satisfies: 950≤m≤1050.

[0068] In order to further ensure the construction of the positive electrode active material satisfying Formula 1, in some optional embodiments, the n satisfies: 750≤n≤850.

[0069] In a third aspect, the present invention provides a positive electrode sheet, comprising a current collector and a positive electrode active layer disposed on at least one surface of the current collector; the positive electrode active layer comprises the positive electrode active material as described in the first aspect.

[0070] It can be understood that the positive electrode active layer also includes a conductive agent and a binder.

[0071] In some embodiments, the positive electrode active material layer includes, by mass percentage: 93-98 wt% of the positive electrode active material, 2-5 wt% of the conductive agent, 2-5 wt% of the binder, and 0-1 wt% of the dispersant. The above system has a more complete electronic conductive network, strong adhesion between particles and between particles and current collectors, which is conducive to the performance at low temperatures and the stability of the system during long-term cycles;

[0072] Exemplarily, the conductive agent can be selected from at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotubes, metal powder, and graphene; the binder can be selected from at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate; the dispersant can be selected from at least one of sodium carboxymethyl cellulose, triethylhexyl phosphoric acid, and sodium dodecyl sulfate.

[0073] The thickness, surface density and thickness of the positive electrode active material layer of the positive electrode sheet are not specifically limited in the present invention. However, in order to balance the battery capacity, cycle life and energy density, in a specific embodiment, the thickness of the positive electrode sheet is 40-120 μm, including but not limited to: 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, etc.; the surface density of the positive electrode sheet is 3-10 mg / cm 2 , including but not limited to: 3.5mg / cm 2 , 4mg / cm 2, 4.5mg / cm 2 , 5mg / cm 2 , 5.5mg / cm 2 , 6mg / cm 2 、6.5mg / cm 2 , 7mg / cm 2 、7.5mg / cm 2 , 8mg / cm 2 、8.5mg / cm 2 , 9mg / cm 2 、9.5mg / cm 2 etc.; the thickness of the positive electrode active material layer is 20-60 μm, specifically including but not limited to: 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, etc.

[0074] In a fourth aspect, the present invention provides a battery, comprising the positive electrode sheet as described in the third aspect.

[0075] It can be understood that the battery of the present invention may further include a negative electrode sheet, a separator and an electrolyte.

[0076] The present invention does not particularly limit the above-mentioned diaphragm, and any known porous structure diaphragm with electrochemical stability and chemical stability can be selected, for example, it can be at least one of glass fiber, non-woven fabric, polyethylene, polypropylene or polyvinylidene fluoride; the diaphragm can be single-layer or multi-layer.

[0077] The present invention does not specifically limit the above-mentioned electrolyte, for example, an electrolyte including an organic solvent and an electrolyte salt is selected. Among them, the organic solvent is used as a medium for transmitting ions in the electrochemical reaction, and can be an organic solvent for battery electrolyte known in the art, such as: one or more of fluorinated carbonates, fluorinated carboxylates, non-fluorinated carbonates, fluorinated carbonates, non-fluorinated carboxylates, fluorinated carboxylates, fluorinated carboxylates, fluorinated ethers, non-fluorinated ethers, and tetrahydrofuran; the electrolyte salt is used as a source of ions, and can be an electrolyte salt for battery electrolyte known in the art, such as: one or more of lithium hexafluorophosphate, bistrifluoromethylsulfonyl imide, and bis(fluorosulfonyl)imide lithium.

[0078] The battery of the present invention can be manufactured according to conventional methods in the art, such as stacking the positive electrode sheet, the separator, and the negative electrode sheet in sequence, assembling the battery cell through a winding process or a stacking process, and then packaging and baking, injecting the electrolyte, and then hot pressing and other processes to obtain the battery.

[0079] The present invention is further described below in conjunction with specific embodiments:

[0080] Example 1

[0081] This example provides a positive electrode active material, the chemical composition of which is Li 1.003 Ni 0.502 Mn 1.498 O 3.793 The positive electrode active material is a single crystal positive electrode active material, and its structural characteristics are shown in Table 1.

[0082] The preparation method thereof comprises the following steps:

[0083] Weigh Ni according to the molar ratio of Li:(Ni+Mn) = 0.9:2 0.5 Mn 1.5 (OH) 4 and Li 2 CO 3 , then Ni 0.5 Mn 1.5 (OH) 4 and Li 2 CO 3 Add to high-speed mixer and mix at a mixing speed of 600 rpm / min for 30 minutes. The mixture was calcined at high temperature in air atmosphere, heated to 1000°C at 2°C / min, and then maintained for 15 hours. After natural cooling, it was crushed by a double-roll crusher and sieved through a 325-mesh sieve to obtain lithium-deficient nickel manganese oxide positive electrode active material (intermediate). The lithium-deficient spinel was weighed before and after crushing to calculate the loss rate.

[0084] The crushed lithium-deficient nickel manganese oxide positive electrode material and Li 2 CO 3 The mixture was added into a high-speed mixer and mixed according to the loss rate (so that the molar ratio of finished product Li: (Ni + Mn) = 1.0: 2) at a mixing speed of 600 rpm / min for 30 min. The mixture was calcined at high temperature in an air atmosphere, and the temperature was increased to 800° C. at a rate of 2° C. / min and maintained for 5 h. After natural cooling, it was crushed by a double-roll crusher and sieved through a 325-mesh sieve to obtain a lithium nickel manganese oxide positive electrode active material.

[0085] Example 2

[0086] This example provides a positive electrode active material, the chemical composition of which is Li 1.004 Ni 0.497 Mn 1.503 W 0.003 O 4.064 The positive electrode active material is a single crystal positive electrode active material. For other parameters, see Table 1.

[0087] The preparation method thereof comprises the following steps:

[0088] Weigh Ni according to the molar ratio of Li:(Ni+Mn) = 0.9:2 0.5 Mn 1.5 (OH)4 and Li 2 CO 3 , then Ni 0.5 Mn 1.5 (OH) 4 and Li 2 CO 3 Add to high-speed mixer and mix at a mixing speed of 600 rpm / min for 30 minutes. The mixture is calcined at high temperature in air atmosphere, heated to 1000°C at 2°C / min, and then maintained for 15 hours. After natural cooling, it is crushed in a double-roll crusher and sieved through a 325-mesh sieve to obtain lithium-deficient nickel manganese oxide positive electrode active material; the lithium-deficient spinel is weighed before and after crushing, and the loss rate is calculated.

[0089] The crushed lithium-deficient nickel manganese oxide positive electrode material and the lithium source with a molar ratio and the designed molar ratio of WO 3 After calculation according to the loss rate (Li: (Ni + Mn): W molar ratio = 1.0: 2: 0.003), the mixture was added to a high-speed mixer for mixing at a mixing speed of 600 rpm / min for 30 minutes. The mixture was calcined at high temperature in an air atmosphere, the temperature was increased to 800°C at 2°C / min, and maintained for 5 hours. After natural cooling, it was crushed by a double-roll crusher and sieved through a 325-mesh sieve to obtain a lithium nickel manganese oxide positive electrode active material.

[0090] Example 3

[0091] This example provides a positive electrode active material, the chemical composition of which is Li 1.005 Ni 0.495 Mn 1.505 Nb 0.003 O 3.996 The positive electrode active material is a single crystal positive electrode active material. For other parameters, see Table 1.

[0092] The difference between the preparation method and Example 2 is that the M source in the secondary sintering is Nb 2 O 5 The secondary sintering temperature was increased to 750°C at 4°C / min and maintained for 6h.

[0093] Example 4

[0094] This example provides a positive electrode active material, the chemical composition of which is LiNi 0.5 Mn 1.5 Mo 0.003 O 4.078 The positive electrode active material is a single crystal positive electrode active material. For other parameters, see Table 1.

[0095] The difference between the preparation method and Example 2 is that the M source in the secondary sintering is MoO 3 The secondary sintering temperature was increased to 850°C at a rate of 1°C / min and maintained for 5h.

[0096] Example 5

[0097] This example provides a positive electrode active material, the chemical composition of which is Li1.002Ni 0.497 Mn 1.503 Ta 0.003 O 4.075 The positive electrode active material is a single crystal positive electrode active material. For other parameters, see Table 1.

[0098] The difference between the preparation method and Example 2 is that the primary sintering is heated to 950°C at 1°C / min and then maintained for 15h; the M source in the secondary sintering is Ta 2 O 5 .

[0099] Example 6

[0100] This example provides a positive electrode active material, the chemical composition of which is Li 1.001 Ni 0.499 Mn 1.501 V 0.003 O 4.005 The positive electrode active material is a single crystal positive electrode active material. For other parameters, see Table 1.

[0101] The difference between the preparation method and Example 2 is that the primary sintering is heated to 1050°C at 4°C / min and then maintained for 11 hours; the M source in the secondary sintering is V 2 O 5 .

[0102] Example 7

[0103] This example provides a positive electrode active material, the chemical composition of which is Li 1.006 Ni 0.503 Mn 1.497 Sb 0.003 O 4.019 The positive electrode active material is a single crystal positive electrode active material. For other parameters, see Table 1.

[0104] The difference between the preparation method and Example 2 is that the M source in the secondary sintering is Sb 2 O 3 .

[0105] Example 8

[0106] This example provides a positive electrode active material, the chemical composition of which is Li 1.002 Ni 0.498 Mn 1.502 W 0.003 O 3.907 The positive electrode active material is a single crystal positive electrode active material. For other parameters, see Table 1.

[0107] The difference between the preparation method and Example 2 is that in the first sintering, Ni is weighed according to the molar ratio of Li: (Ni + Mn) = 0.8:2. 0.5 Mn 1.5 (OH) 4 and Li 2 CO 3 .

[0108] Example 9

[0109] This example provides a positive electrode active material, the chemical composition of which is Li 1.003 Ni 0.497 Mn 1.503 W 0.003 O 4.055 The positive electrode active material is a single crystal positive electrode active material. For other parameters, see Table 1.

[0110] The difference between the preparation method and Example 2 is that in the first sintering, Ni is weighed according to the molar ratio of Li: (Ni + Mn) = 0.85:2. 0.5 Mn 1.5 (OH) 4 and Li 2 CO 3 .

[0111] Example 10

[0112] This example provides a positive electrode active material, the chemical composition of which is Li 1.001 Ni 0.503 Mn 1.497 W 0.003 O 4.082 The positive electrode active material is a single crystal positive electrode active material. For other parameters, see Table 1.

[0113] The difference between the preparation method and Example 2 is that in the first sintering, Ni is weighed according to the molar ratio of Li: (Ni + Mn) = 0.95:2. 0.5 Mn 1.5 (OH) 4 and Li 2 CO 3 .

[0114] Comparative Example 1

[0115] This example provides a positive electrode active material, the chemical composition of which is Li 1.002 Ni 0.503 Mn 1.497 O 3.815 The positive electrode active material is a single crystal positive electrode active material. For other parameters, see Table 1.

[0116] The preparation method thereof comprises the following steps:

[0117] Weigh Ni according to the molar ratio of Li:(Ni+Mn) = 1:2 0.5 Mn 1.5 (OH) 4 and Li 2 CO 3 , then Ni 0.5 Mn 1.5 (OH) 4 and Li 2 CO 3 Add the mixture to a high-speed mixer and mix at a mixing speed of 600 rpm / min for 30 minutes. The mixture is calcined at high temperature in an air atmosphere, heated to 1000°C at 2°C / min, and then maintained for 15 hours. After natural cooling, it is crushed in a double-roll crusher and sieved through a 325-mesh sieve to obtain a lithium nickel manganese oxide positive electrode active material.

[0118] The single crystal lithium nickel manganese oxide positive electrode material was sintered twice and added to a high-speed mixer for mixing at a mixing speed of 600 rpm / min for 30 minutes. The mixture was calcined at high temperature in an air atmosphere, heated to 800°C at 2°C / min, maintained for 5 hours, and crushed in a double-roll crusher after natural cooling, and the lithium nickel manganese oxide positive electrode active material was obtained through a 325-mesh sieve.

[0119] Comparative Example 2

[0120] This example provides a positive electrode active material, the chemical composition of which is Li 1.001 Ni 0.5 Mn 1.5 W 0.003 O 4.084 The positive electrode active material is a single crystal positive electrode active material. For other parameters, see Table 1.

[0121] The difference between the preparation method and comparative example 1 is that WO with a molar ratio of Li:(Ni+Mn):M source = 1.0:2:0.003 is added in the secondary sintering. 3 .

[0122] Comparative Example 3

[0123] This example provides a positive electrode active material, the chemical composition of which is Li 1.003 Ni 0.501 Mn 1.499 Nb 0.003 O 4.020 The positive electrode active material is a single crystal positive electrode active material. For other parameters, see Table 1.

[0124] The difference between the preparation method and comparative example 1 is that Nb with a molar ratio of Li:(Ni+Mn):M source = 1.0:2:0.003 is added in the secondary sintering. 2 O 5.

[0125] Comparative Example 4:

[0126] This example provides a positive electrode active material, the chemical composition of which is Li 1.003 Ni 0.504 Mn 1.496 Mo 0.003 O 4.091 The positive electrode active material is a single crystal positive electrode active material. For other parameters, see Table 1.

[0127] The difference between the preparation method and comparative example 1 is that MoO with a molar ratio of Li:(Ni+Mn):M source = 1.0:2:0.003 is added in the secondary sintering. 3 .

[0128] Comparative Example 5

[0129] This example provides a positive electrode active material, the chemical composition of which is Li 1.004 Ni 0.505 Mn 1.495 Ta 0.003 O 4.041 The positive electrode active material is a single crystal positive electrode active material. For other parameters, see Table 1.

[0130] The difference between the preparation method and comparative example 1 is that the Ta is added in the secondary sintering with a molar ratio of Li:(Ni+Mn):M source = 1.0:2:0.003 2 O 5 .

[0131] Comparative Example 6

[0132] This example provides a positive electrode active material, the chemical composition of which is Li 1.002 Ni 0.499 Mn 1.501 V 0.003 O 4.027 The positive electrode active material is a single crystal positive electrode active material. For other parameters, see Table 1.

[0133] The difference between the preparation method and comparative example 1 is that V is added in a molar ratio of Li:(Ni+Mn):M source = 1.0:2:0.003 during the secondary sintering. 2 O 5 .

[0134] Comparative Example 7

[0135] This example provides a positive electrode active material, the chemical composition of which is Li 1.005 Ni 0.501 Mn 1.499 Sb 0.003 O 3.950The positive electrode active material is a single crystal positive electrode active material. For other parameters, see Table 1.

[0136] The difference between the preparation method and comparative example 1 is that Sb with a molar ratio of Li:(Ni+Mn):M source = 1.0:2:0.003 is added in the secondary sintering. 2 O 3 .

[0137] The following tests were performed on the positive electrode active materials of the above embodiments and comparative examples:

[0138] 1. The microscopic morphology of the positive electrode active materials of the above-mentioned embodiments and comparative examples was observed by SEM, wherein: Figure 1 The SEM image of the positive electrode active material of Example 1 is shown. Figure 2 The SEM image of the positive electrode active material of Comparative Example 1 is shown. Figure 3 The SEM image of the positive electrode active material of Example 2 is shown. Figure 4 This is a SEM image of the positive electrode active material of Comparative Example 2; by comparison, it can be seen that the positive electrode active materials of lithium nickel manganese oxide in Examples 1 and 2 present a truncated octahedral structure, and there is agglomeration between the particles of Example 1. This is because Example 1 does not add fluxing elements (M), which cannot reduce the surface energy of the surface of lithium nickel manganese oxide, resulting in poor dispersion of lithium nickel manganese oxide, and cannot control the directional repair of the crystal plane of lithium nickel manganese oxide, resulting in excessive exposure of the (100) and (110) crystal planes of the overall material, and more holes appear, which will affect the electrochemical stability of lithium nickel manganese oxide. Comparative Examples 1-2 present octahedral lithium nickel manganese oxide, with a smooth surface, basically existing in the form of a regular octahedron. By adding fluxing elements, the surface energy of lithium nickel manganese oxide is well improved, the dispersion is good, and the (100) and (110) crystal planes are directionally repaired, and no holes are generated.

[0139] 2. The crystal structures of the positive electrode active material powders of the above embodiments and comparative examples were tested by XRD.

[0140] Figure 5 The XRD diffraction patterns of Example 1 and Comparative Example 1 are shown in Table 1. (111) + (222) / I (400) + (440) The value of is significantly decreased, indicating that the (100) and (110) crystal planes are more exposed. By comparing the XRD diffraction patterns of the embodiment and the comparative example, it can be seen that by adding flux elements, lithium nickel manganese oxide with different exposed crystal planes is synthesized.

[0141] 3. X-ray photoelectron spectroscopy (XPS) was used to test the manganese ion content of the positive electrode active material: the positive electrode active materials of the embodiment and the comparative example were etched, and then the valence state and content of manganese element of samples with different etching depths were tested. Mn was obtained according to data fitting. 4+ / Mn 3+ The ratio of Mn 4+ / Mn 3+ The ratio of is defined as C1, and the Mn 4+ / Mn 3+ The ratio of C2 is defined as C2, and the value of C2-C1 is defined as the Mn content of the positive electrode active material. 3+ The degree of gradient change.

[0142] Application Example 1

[0143] The positive electrode sheet is prepared using the positive electrode active materials of the above embodiments and comparative examples, comprising the following steps:

[0144] The above examples and comparative examples were added to an appropriate amount of NMP in a ratio of positive electrode active material: conductive agent (Super P): binder (PVDF) = 94.5:3:2.5, and mixed and homogenized using a degassing machine. The mixed slurry was coated on both sides of the aluminum foil to obtain a positive electrode sheet. The single-sided surface density of the positive electrode sheet was 8 mg / cm 2 .

[0145] Application Example 2

[0146] The preparation of a battery using the above-mentioned positive electrode sheet comprises the following steps:

[0147] Lithium-ion batteries were prepared using the nickel-manganese-oxide positive electrode material of the embodiment and the nickel-manganese-oxide positive electrode material of the comparative example as positive electrode materials. The lithium-ion battery is mainly composed of the positive electrode sheet, negative electrode sheet, separator and electrolyte of Application Example 1. The negative electrode sheet is a lithium sheet. The electrolyte is a mixed liquid of dimethyl carbonate, diethyl carbonate and ethyl carbonate in a volume ratio of 1:1:1 as solvent, and 1 mol / L LiPF is added. 6 The positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence to obtain a battery cell, and then a lithium-ion battery is obtained through baking, liquid injection, formation and packaging processes.

[0148] Performance Testing:

[0149] The electrical properties of each lithium-ion battery assembled in Application Example 2 were tested separately (the results are shown in Table 2): the following steps were included:

[0150] CC+CV charge and discharge test was carried out with a voltage window of 3.5-4.85V (vs.Li+ / Li). The specific test steps were 0.1C charge and discharge cycles for 2 cycles, 0.33C charge and 2C discharge cycles for 100 cycles, and 0.33C charge and 3C discharge cycles for 5 cycles. The cycle retention rate for 100 cycles was the percentage of the 2C discharge capacity at the 100th cycle to the 2C discharge capacity at the 1st cycle; the 4V platform proportion was the ratio of the discharge capacity below 4.4V in the first cycle to the total capacity of the first discharge; the 2C / 0.1C rate percentage was the ratio of the 2C discharge capacity in the first cycle to the 0.1C discharge capacity in the first cycle.

[0151] Table 2:

[0152]

[0153]

[0154] It can be seen from Table 1 that compared with the comparative example, the battery discharge capacity and rate performance of the embodiment are better. From the perspective of contribution to the 4V platform capacity, the lithium nickel manganese oxide of the embodiment is slightly higher. This may be because the lithium nickel manganese oxide of the embodiment forms more lithium-rich phase and disordered phase lithium nickel manganese oxide at the surface interface, which is also one of the reasons for the better rate performance and discharge capacity.

[0155] Furthermore, it can be seen from Table 1 that the values ​​of Examples C1 and C2 have obvious changes, and the difference between C2 and C1 is large, indicating that the Mn content of the material as a whole increases from the outside to the inside. 4+ / Mn 3+ The valence state of the material changes greatly, with an obvious gradient change; the values ​​of C1 and C2 in other embodiments different from those in Example 1 are obviously relatively small, indicating that the coating of the high-valence element M causes the surface lithium nickel manganese oxide structure to be transformed into a disordered phase; similarly, the difference between C2 and C1 in the comparative example is small, indicating that the material as a whole changes from the outside to the inside of Mn 4+ / Mn 3+ The valence state changes slightly, and there is no obvious gradient change, indicating that during the secondary sintering process, the flux element M diffuses and enters the bulk. The flux element M in the embodiment mainly plays a role in repairing a directional crystal plane during the secondary sintering process. Since it is difficult to replace the lithium-deficient spinel with Ni / Mn in the repair process, it is concentrated on the surface of the material.

[0156] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A positive electrode active material, characterized in that: The positive electrode active material satisfies the following formula 1: Among them, I (111) ,I (222) ,I (400) and I (440) Both are not 0.

2. The positive electrode active material according to claim 1, characterized in that The positive electrode active material includes trivalent manganese ions and tetravalent manganese ions, and the mass ratio of the trivalent manganese ions to the tetravalent manganese ions increases from the center to the outer surface of the positive electrode active material.

3. The positive electrode active material according to claim 2, characterized in that The chemical composition of the positive electrode active material includes: Li a Ni b Mn c M d O 4-h ; Among them, 1.0≤a≤1.006, 0.495≤b≤0.505, 1.495≤c≤1.505, 0≤d≤0.003, -0.082<h<0.21, b+c=2, and M is selected from at least one of W, Mo, Ta, Nb, V, and Sb.

4. The positive electrode active material according to claim 2 or 3, characterized in that The disorder degree of the positive electrode active material is 6%-9%.

5. A method for preparing a positive electrode active material according to any one of claims 1 to 4, characterized in that: The following steps are involved: The mixed material including the nickel manganese hydroxide precursor and the first lithium source is heated to m°C at a heating rate of 1-5°C / min in an oxygen-containing atmosphere, and sintered once to obtain an intermediate; wherein the first lithium source is calculated as lithium element, the nickel manganese hydroxide precursor is calculated as the sum of nickel element and manganese element, and the molar ratio of the nickel manganese hydroxide precursor to the first lithium source is 2:0.8-0.95; The mixed material including the intermediate second lithium source is heated to n°C at a heating rate of 1-5°C / min in an oxygen-containing atmosphere for a second time and sintered to obtain the positive electrode active material, wherein n is less than m.

6. The preparation method according to claim 5, characterized in that: The first lithium source is calculated as lithium element, the nickel manganese hydroxide precursor is calculated as the sum of nickel element and manganese element, and the molar ratio of the nickel manganese hydroxide precursor to the first lithium source is 2:0.85-0.

9.

7. The preparation method according to claim 5, characterized in that: The m satisfies: 950≤m≤1050.

8. The preparation method according to claim 5, characterized in that: The n satisfies: 750≤n≤850.

9. A positive electrode sheet, characterized in that: It comprises a current collector and a positive electrode active layer arranged on at least one surface of the current collector; the positive electrode active layer comprises the positive electrode active material according to any one of claims 1 to 4.

10. A battery, characterized in that: Including the positive electrode sheet as described in claim 9.

Citation Information

Cited By

  • Secondary battery

    CN120727740A

  • A secondary battery

    CN120727740B

  • Positive electrode active material and preparation method thereof, lithium ion battery and electric equipment

    CN121123222A

  • Positive electrode active material and preparation method therefor, positive electrode sheet, and battery

    WO2026144165A1